THE ROLE OF PRODUCTION MANAGEMENT IN CANNING LEMURU FISH (SARDINELLA LONGICEPS) IN TOMATO SAUCE MEDIA AT PT. SARANA TANI PRATAMA JEMBRANA-BALI - HM, Rahmayati; Ahmad, A. Rahmawati; Ratnawati, Ratnawati; Ahmad, Ilham (ITScience (Information Technology and Science), 2022)
The writing of this final project aims to determine the role of production management in canning lemuru fish. The data sources used are primary data, and secondary data and data collection methods used, namely, interview methods, observations, literature studies, and data analysis using qualitative descriptive analysis. The Role of Production Management at PT. Tani Pratama facilities starting from planning, implementation and supervision have run optimally and have been fully implemented in accordance with standard operational procedures (SOPs) in the company. The results obtained are lemuru fish canning management at PT. Sarana Tani Pratama has been fully implemented, first planning consisting of 4 items, namely raw material inventory, production scheduling, production equipment, production capacity, second, implementation which includes activities ranging from receiving raw materials to marketing, third supervision, in the process of canning lemuru fish (Sardinella Longiceps) carried out by PT. Primary Farm Facilities that need to be supervised and controlled during the production process are all forms of work carried out by employees in accordance with standard operational procedures (SOPs).